Amine catalyst for preparing stable polyurethane foam system as well as preparation method and application of amine catalyst

By preparing amine catalysts with specific structures and applying them in polyurethane foam systems, the problems of high stability and cost of traditional catalysts are solved, and the high stability and applicability of the polyurethane foam system is achieved, which is suitable for spraying applications.

CN119264356APending Publication Date: 2025-01-07FUJIAN YUECHUN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411136209.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional amine catalysts are unstable when used with certain foaming agents, especially in halogenated olefin foaming agents, resulting in stability and storage life problems of polyurethane foam systems, and the existing improved methods are high in cost or low in activity, and do not Suitable for spraying applications.

Method used

A novel amine catalyst is provided, and its structural formula is a specific group combination and is prepared by reacting a specific metal catalyst with formaldehyde at a certain temperature to improve the stability and reactivity of the catalyst. The catalyst is used to prepare a polyurethane foam system, including polyol resin, isocyanate and foaming agent, and improves the stability of the system by optimizing the molar ratio and reaction conditions.

Benefits of technology

This amine catalyst only loses part of its reactivity after four weeks, significantly improving the stability of the polyurethane foam system, suitable for spraying applications, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264356A_ABST
    Figure CN119264356A_ABST
Patent Text Reader

Abstract

The invention relates to an amine catalyst for preparing a stable polyurethane foam system as well as a preparation method and application of the amine catalyst, the structural general formula of the amine catalyst is # imgabs0, the polyurethane foam system prepared from the amine catalyst has excellent stability, and only part of reactivity is lost after four weeks; good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane preparation, and particularly relates to an amine catalyst for preparing a stable polyurethane foam system, and a preparation method and application thereof. Background Art

[0002] Polyurethane foam compositions are usually prepared by reacting isocyanates and polyol resin blends. The polyol resin blend includes, but is not limited to, components such as water, flame retardants, blowing agents, surfactants that stabilize the foam, and catalysts that are used to promote the reaction of isocyanates with polyols to produce carbamates, with water to produce CO2 and urea, and with excess isocyanates to produce isocyanurates (trimers).

[0003] The blowing agent in the polyol resin blend is usually a liquid or gas with a boiling point low enough to be vaporized by the heat released during the polymerization reaction. Blowing agents that can be used to prepare insulating polyurethane foams include, but are not limited to, hydrofluorocarbons (HFCs), hydrofluoroolefins (HFOs), hydrofluorochloroolefins (HFCOs), hydrochlorofluorocarbons (HCFCs), formates, ketones (such as acetone), and hydrocarbons. Traditional amine catalysts are unstable when used with certain blowing agents, especially halogenated olefin blowing agents such as trans-1-chloro-3,3,3-trifluoropropene (known as 1233zd (E)) or cis-1,1,1,3,3,3-hexafluoro-2-butene (known as 1366mzz (Z)), which react with amines due to their activated double bonds. In addition, the fluoride ions eliminated from the HFO molecules attack the silicon atoms in the organosilicon surfactant, degrading the surfactant, which reduces the surfactant performance and weakens the cell structure of the resulting foam. Various attempts have been made in the prior art to improve the shelf life of blends containing amine and halogenated olefin blowing agents without affecting their ability to catalyze polyurethane foam formulations at a reasonable rate, with the introduction of sterically hindered amine catalysts increasing the stability of the HFO system.

[0004] CN11799301A discloses a polyol blend, which includes one or more active hydroxyl compounds, an organosilicon surfactant, a halogenated olefin blowing agent and an amine catalyst. However, the raw material source of the amine catalyst is scarce, the two-step process has a medium yield, and the production cost is high.

[0005] US9550854 discloses hindered amine catalysts, including but not limited to dicyclohexylmethylamine, diisopropylethylamine and dicyclohexyl, which can reduce the degradation of HFO blowing agents, but the catalyst activity is low and is not suitable for spray foam applications.

[0006] Therefore, there is a continuing need to develop amine catalysts at an economical cost that can promote a rapid reaction between isocyanate and polyol resin blends without affecting the storage stability of the blends when HFO blowing agents are used. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide an amine catalyst for preparing a stable polyurethane foam system, a preparation method and application thereof. The polyurethane foam system prepared using the amine catalyst has excellent stability and only loses a part of its reactivity after four weeks, and has good application prospects.

[0008] The present invention provides an amine catalyst for preparing a stable polyurethane foam system, characterized in that the general structural formula of the amine catalyst is: Wherein, R1 is independently selected from one or more of the following groups: hydrogen, methyl, ethyl;

[0009] R2 is independently selected from one or more of the following groups: methyl, tert-butyl;

[0010] X is independently selected from one or more of the following groups: -O-, -N(CH3)-;

[0011] p is 0 or 1;

[0012] n and m are 0-4.

[0013] Preferably, when X is -O-, R1 is hydrogen or methyl, R2 is hydrogen, and R3 is tert-butyl; or when X is -O-, R1 is hydrogen or methyl, R2 is methyl or ethyl, and R3 is methyl; or when X is -N(CH3)-, R1 is hydrogen, R2 is hydrogen, and R3 is tert-butyl.

[0014] Most preferably, the amine catalyst is n is 0-2.

[0015] The present invention also provides a method for preparing an amine catalyst for preparing a stable polyurethane foam system, comprising the following steps:

[0016] The raw material A is reacted with excess formaldehyde at 100-140°C in the presence of a metal catalyst.

[0017] Preferably, the raw material A comprises a combination of ethylene glycol, diethylene glycol, triethylene glycol or methyldiethanolamine and tert-butylamine in a molar ratio of 1:4-6 or XTJ-568 (Huntsman Corporation).

[0018] The structural formula of XTJ-568 is as follows:

[0019]

[0020] Preferably, the metal catalyst is a Ni-Cu-Cr catalyst.

[0021] The invention also provides an application of an amine catalyst in preparing a polyurethane foam system.

[0022] Furthermore, the polyurethane foam system comprises a polyol resin blend and at least one polyisocyanate; wherein the polyol resin blend comprises the following components in parts by mass:

[0023]

[0024]

[0025] Preferably, the general formula of the polyisocyanate is Q(NCO)a, wherein a is 2-5, and Q is an aliphatic hydrocarbon group containing 2-18 carbon atoms, an alicyclic hydrocarbon group containing 5-10 carbon atoms, an aromatic aliphatic hydrocarbon group containing 8-13 carbon atoms, or an aromatic hydrocarbon group containing 6-15 carbon atoms.

[0026] The polyisocyanate includes, but is not limited to, ethylene diisocyanate; 1,4-tetramethylene diisocyanate; 1,6-hexamethylene diisocyanate; 1,12-dodecane diisocyanate; cyclobutane-1,3-diisocyanate; cyclohexane-1,3-isocyanate and 1,4-diisocyanate, or a mixture of isomers; isophorone diisocyanate; 2,4-hexahydrotoluene diisocyanate or 2,6-hexahydrotoluene diisocyanate or a mixture of isomers; dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI, or HMDI); 1,3-phenylene diisocyanate or 1,4-phenylene diisocyanate; 2,4-toluene diisocyanate or 2,6-toluene diisocyanate or a mixture of isomers (TDI); diphenylmethane-2,4'-diisocyanate ester and / or -4,4'-diisocyanate (MDI); naphthylene-1,5-diisocyanate; triphenylmethane-4,4',4"-triisocyanate; polyphenyl-polymethylene-polyisocyanates of the type described below, which can be obtained by condensation of aniline with formaldehyde and subsequent phosgenation (crude MDI); norbornane diisocyanate; m- and p-isocyanatophenylsulfonyl isocyanate; perchlorinated aromatic polyisocyanates; modified polyisocyanates containing carbodiimide groups, urethane groups, allomethyl groups, isocyanurate groups, urea groups or biuret groups; polyisocyanates obtained by telomerization; polyisocyanates containing ester groups; and polyisocyanates containing polymeric fatty acid groups. Those skilled in the art will recognize that mixtures of the above-mentioned polyisocyanates can also be used.

[0027] Isocyanate terminated prepolymers can also be used to prepare polyurethanes.Isocyanate terminated prepolymers can be prepared by reacting an excess of a polyisocyanate or a mixture thereof with a small amount of an active hydrogen containing compound as determined by the well known Zerewitinoff test.

[0028] Preferably, the polyol includes, but is not limited to, polyalkylene ether polyol, polyester polyol, polymer polyol, non-flammable polyol such as phosphorus-containing polyol or halogen-containing polyol. The polyol can be used alone or in a suitable combination as a mixture.

[0029] The polyalkylene ether polyols include poly(alkylene oxide) polymers such as polyethylene oxide and polypropylene oxide polymers and copolymers having terminal hydroxyl groups derived from polyols (including diols and triols); for example, ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, pentaerythritol, glycerol, diglycerol, trimethylolpropane and similar low molecular weight polyols.

[0030] The polyester polyols include, but are not limited to, those produced by reacting dicarboxylic acids with excess glycols, such as adipic acid with ethylene glycol or butanediol, or those produced by reacting lactones with excess glycols, such as caprolactone with propylene glycol. In addition to polyalkylene ether polyols and polyester polyols, polymer polyols are also suitable for the present invention. Polymer polyols are used in polyurethane materials to increase deformation resistance, such as to improve the load-bearing properties of foams or materials. Examples of polymer polyols include, but are not limited to, graft polyols or polyurea-modified polyols (Polyharns toff Dispersion polyols). Graft polyols contain triols, in which vinyl monomers are graft copolymerized. Suitable vinyl monomers include, for example, styrene, or acrylonitrile. Polyurea-modified polyols are polyols containing polyurea dispersions formed by reacting diamines and diisocyanates in the presence of polyols. A variant of polyurea-modified polyols is polyisocyanate polyaddition (PIPA) polyols, which are formed by in-situ reaction of isocyanates and alkanolamines in polyols.

[0031] The non-flammable polyol may be, for example, a phosphorus-containing polyol which can be obtained by adding an alkylene oxide to a phosphoric acid compound. The halogen-containing polyol may be, for example, those obtainable by ring-opening polymerization of epichlorohydrin or trichlorobutylene oxide.

[0032] Preferably, the surfactant includes an emulsifier or a foam stabilizer, such as silicone surfactants known in the art such as polysiloxane, and amine salts of various fatty acids, such as diethylamine oleate or diethanolamine stearate, and sodium salt of ricinoleic acid.

[0033] Preferably, the foaming agent is LBA foaming agent.

[0034] Preferably, the flame retardant is a phosphate flame retardant, chlorinated paraffin or melamine powder.

[0035] Furthermore, the polyol resin blend further comprises 0.01-5 parts of a foaming solubilizer.

[0036] In some cases, the amine catalysts of the present invention may be combined with two or more other disclosed catalysts, such as As well as acid-terminated catalysts, useful acids include but are not limited to formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, neopentanoic acid, hexanoic acid, 2-ethylhexylcarboxylic acid, neohexanoic acid, octanoic acid, neooctanoic acid, heptanoic acid, neoheptanoic acid, nonanoic acid, neononanoic acid, decanoic acid, neodecanoic acid, undecanoic acid, neoundecanoic acid, dodecanoic acid, neododecanoic acid, myristic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, benzoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, glycolic acid, lactic acid, tartaric acid, citric acid, malic acid and salicylic acid.

[0037] Beneficial Effects

[0038] The polyurethane foam system prepared by using the amine catalyst of the present invention has excellent stability and only loses a part of its reactivity after four weeks, and has good application prospects. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0040] Example 1

[0041] 200 g of 4*4 mm metal catalyst (Ni-Cu-Cr) was loaded in a 250 mL fixed bed reactor, hydrogen was introduced into the reactor at a rate of 185 ml / min using a mass flow meter, the pressure was controlled at 130 kg, the temperature was raised to 220° C., ethylene glycol (40 g / h) and tert-butylamine (188 g / h) were continuously introduced into the reactor (molar ratio was 1:4) using an HPLC pump, and after removing excess tert-butylamine, the product was reacted with 20% excess formaldehyde and hydrogen at 120° C. and 130 kg in the same reactor. After the crude product was distilled, compound I was obtained with a purity greater than 99%.

[0042] The structural formula of the compound I is

[0043] Example 2

[0044] 200g of 4*4mm metal catalyst (Ni-Cu-Cr) was loaded in a 250mL fixed bed reactor, hydrogen was introduced into the reactor at a rate of 67 ml / min using a mass flow meter, the pressure was controlled at 130 kg, the temperature was raised to 220°C, diethylene glycol (20g / h) and tert-butylamine (68g / h) were continuously introduced into the reactor (molar ratio was 1:5) using an HPLC pump, and after removing excess tert-butylamine, the product was reacted with 20% excess formaldehyde and hydrogen at 120°C and 130 kg in the same reactor. After distilling the crude product, compound II was obtained, with a structural formula of and a purity of more than 98%.

[0045] The structural formula of the compound II is

[0046] Example 3

[0047] 200 g of 4*4 mm metal catalyst (Ni-Cu-Cr) was loaded in a 250 mL fixed bed reactor, hydrogen was introduced into the reactor at a rate of 43 ml / min using a mass flow meter, the pressure was controlled at 130 kg, the temperature was raised to 225° C., triethylene glycol (15 g / h) and tert-butylamine (44 g / h) were continuously introduced into the reactor (molar ratio was 1:6) using an HPLC pump, and after removing excess tert-butylamine, the product was reacted with 20% excess formaldehyde and hydrogen at 120° C. and 130 kg in the same reactor. After the crude product was distilled, compound III was obtained with a purity greater than 96%.

[0048] The structural formula of the compound III is

[0049] Example 4

[0050] 200 g of 4*4 mm metal catalyst (Ni-Cu-Cr) was loaded in a 250 mL fixed bed reactor, hydrogen was introduced into the reactor at a rate of 67 ml / min using a mass flow meter, the pressure was controlled at 130 kg, the temperature was raised to 215° C., methyldiethanolamine (20 g / h) and tert-butylamine (67 g / h) were continuously introduced into the reactor (molar ratio of 1:5) using an HPLC pump, and after removing excess tert-butylamine, the product was reacted with 20% excess formaldehyde and hydrogen at 120° C. and 130 kg in the same reactor. After the crude product was distilled, compound IV was obtained with a purity greater than 99%.

[0051] The structural formula of the compound IV is

[0052] Example 5

[0053] 200 g of 4*4 mm metal catalyst was loaded into a 250 mL fixed bed reactor, hydrogen was introduced into the reactor at a rate of 78 mL / min using a mass flow meter, the pressure was controlled at 130 kg, the temperature was raised to 120° C. XTJ-568 (Huntsman) and excess 20% formaldehyde were introduced into the reactor using an HPLC pump, and after removing methanol and water, compound V was obtained with a purity of 98%.

[0054] The structural formula of the compound V is n is 0-2.

[0055] Comparative Example 1

[0056] 200 g of 4*4 mm metal catalyst was loaded into a 250 mL fixed bed reactor. Hydrogen was introduced into the reactor at a rate of 78 mL / min using a mass flow meter. The pressure was controlled at 130 kg. The temperature was raised to 120 °C. The HPLC pump was used to pump (Huntsman Corporation) and excess 20% formaldehyde were introduced into the reactor, and after removing methanol and water, compound V was obtained with a purity of 98%.

[0057] The structural formula is as follows,

[0058] x=2, y+z=1-2.

[0059] The structural formula of the compound VI is n is 0-2.

[0060] Example 6

[0061] This example describes the performance of the amine catalyst prepared in Example 5 in a polyurethane system for spray foam with an HFO blowing agent. The performance and pot life stability of the amine catalyst were performed using the foam formulations in Table 1 (see below). The catalyst reactivity in the spray polyurethane system was evaluated using a free-rise cup foam sample using a FOAMAT sonar take-off rate (ROR) device. The FOAMAT standard software generates a graph of height versus time and a graph of speed versus time. These graphs can be used to compare the relative reactivity of different catalyst formulations. MDI polyurethane foams were prepared by traditional manual mixing. The experiment used 5 parts of a new amine catalyst. The pot life study of the following formulations was tested in a hot air oven at 50°C for 4 weeks. The take-off rate performance was monitored using FOAMAT sonar. The polyurethane formulations in parts by weight are:

[0062] Table 1: Formulations used in this example

[0063] Formulations Mass parts (pphp) Polyols 100 Flame retardants 23 Surfactants 1.0 water 2.5 Amine Catalyst V 5 HFO 10 HFO solubilizer 3.0

[0064] Polyol: A mixture of polyester (Stepanpol PS3152) from Stepan and polyether polyol (NJ-M330) from Jurong Ningwu New Materials Co., Ltd. (mass ratio is 1:1).

[0065] Flame retardant: WSFR-TCPP, a phosphate flame retardant produced by Wansheng Co., Ltd.

[0066] Surfactant: Shanghai Xinrui New Materials Loca S193 surfactant.

[0067] HFO: from Honeywell LBA.

[0068] HFO solubilizer: from Shanghai Xinrui New Materials XR PM301.

[0069] The above components were mixed in a 500 ml plastic beaker, and Huntsman Suprasec-5005MDI was added thereto and mixed at 4000 RPM for 3 seconds using a laboratory dispenser made in China. Immediately after mixing, the paper cup was placed under the sonar of a Foamat machine (FOAMAT Messtechnik GmbH), and the foam rise curve was obtained using a software device, and the ROR curve for 120 seconds was measured. Three samples of the same formulation were stored in three sealed aluminum bottles and heated at 50°C for four weeks. The ROR curve was monitored at 0, the first, the second and the fourth week. The summary of the observations is listed in Table 2.

[0070] Table 2 Time (in seconds) to reach 80% of maximum height in manual mixing experiments with catalysts

[0071] Heat aging time (weeks) Time (seconds) %change 0 15.1 0.0 1 15.6 3.3 2 16.9 11.9 4 18 19.2

[0072] As is evident from Table 2, it takes 4 weeks for the catalyst to lose its reactivity performance at 50°C. The catalyst has excellent stability for 2 weeks at 50°C. After 2 weeks at 50°C, it begins to lose its reactivity. In the fourth week, at 50°C, it has lost almost 19% of its original reactivity. The chemical reaction of water and polyols with isocyanates is typically catalyzed by both amines and metal catalysts. There are many possible decomposition pathways that can occur in a fully formulated polyurethane system, which can lead to potential changes in the reactivity of the system over time. For example, it has been previously shown that amine catalysts can catalyze the decomposition of HCFCs in polyurethane foam formulations, resulting in the production of hydrofluoric acid or hydrochloric acid, which can further decompose the polyester polyols, flame retardants, silicone surfactants, the amines or metal catalysts, and lead to a loss of effectiveness of the blowing agent. Hydrofluoroolefins such as HFCO-1233zd(E) can be additionally challenging because the sp2 carbon of the olefin has an electrophilic nature, making it more easily coordinated to the amine catalyst, leading to a variety of possible decomposition pathways.

[0073] Example 7

[0074] The pot life study was conducted in the same manner as in Example 6 using Compound I in Example 1 as the amine catalyst, and the results shown in Table 3 were obtained.

[0075] Table 3 Time (in seconds) to reach 80% of maximum height in manual mixing experiments for catalysts

[0076] Heat aging time (weeks) Time (seconds) %change 0 17.6 0.0 1 18.9 8.2 2 22.1 18.5 4 24.2 28.7

[0077] As shown in Table 3, the Compound I lost significant reactivity over a period of four weeks at 50° C. After four weeks of aging, the rise time increased by 37% from its original value.

[0078] Example 8

[0079] The pot life study was conducted in the same manner as in Example 6 using Compound II in Example 2 as an amine catalyst, and the results shown in Table 4 were obtained.

[0080] Table 4 Time to reach 80% of maximum height in manual mixing experiments for catalysts (in seconds)

[0081] Heat aging time (weeks) Time (seconds) %change 0 18.2 0.0 1 20.2 10.2 2 26.6 36.2 4 38.9 59.6

[0082] As shown in Table 4, the Compound II lost significant reactivity over a period of four weeks at 50° C. After four weeks of aging, the rise time increased by 114% from its original value, which may be due to the unconverted materials in the product affecting the stability of the HFO.

[0083] Example 9

[0084] The pot life study was conducted in the same manner as in Example 5 using Compound III in Example 3 as an amine catalyst, and the results shown in Table 5 were obtained.

[0085] Table 5 Time (in seconds) to reach 80% of maximum height in manual mixing experiments for catalysts

[0086] Heat aging time (weeks) Time (seconds) %change 0 18.1 0.0 1 22.8 8.5 2 28.4 28.2 4 39.2 49.5

[0087] As shown in Table 5, the compound III lost significant reactivity over a period of four weeks at 50° C. After four weeks of aging, the rise time increased by 116% from its original value, which may be due to the unconverted materials in the product affecting the stability of the HFO.

[0088] Example 10

[0089] The pot life study was conducted in the same manner as in Example 5 using Compound IV in Example 4 as an amine catalyst, and the results shown in Table 6 were obtained.

[0090] Table 6 Time to reach 80% of maximum height in manual mixing experiments for catalysts (in seconds)

[0091] Heat aging time (weeks) Time (seconds) %change 0 17.5 0.0 1 18.1 7.8 2 21.8 15.7 4 23.6 28.9

[0092] As shown in Table 6, the Compound IV lost 28.9% of its reactivity over a period of four weeks at 50°C. After four weeks of aging, the rise time increased by 34% from its original value.

[0093] Comparative Example 2

[0094] The pot life study was conducted in the same manner as in Example 5 using Compound VI in Comparative Example 1 as an amine catalyst, and the results shown in Table 7 were obtained.

[0095] Table 7 Time (in seconds) to reach 80% of maximum height in manual mixing experiments for catalysts

[0096] Heat aging time (weeks) Time (seconds) %change 0 16.8 0.0 1 24.9 15.2 2 35.2 34.8 4 41.6 60.1

[0097] As shown in Table 7, the compound VI lost significant reactivity over a period of four weeks at 50° C. After four weeks of aging, the rise time increased by 147% from its original value, which may be due to the unconverted materials in the product affecting the stability of the HFO.

[0098] Comparative Example 3

[0099] The pot life study was conducted in the same manner as in Example 5 using N,N,N',N",N"-pentamethyldiethylenetriamine (PMDETA), a standard catalyst used in polyurethane systems for rigid spray foams, and the results shown in Table 8 were obtained.

[0100] Table 8 Time to reach 80% of maximum height in manual mixing experiments for catalysts (in seconds)

[0101] Heat aging time (weeks) Time (seconds) %change 0 15.1 0.0 1 22.9 52.0 2 31.5 108.6 4 50.7 235.8

[0102] The catalyst rapidly loses its activity as shown in Table 8. This commercial catalyst is too unstable to be used with HFO blowing agents.

[0103] Comparative Example 4

[0104] A pot life study was conducted in the same manner as in Example 5 using a reactive catalyst used in a polyurethane system for rigid spray foam (35 wt % tetramethylguanidine and 65 wt % succinic acid salt mixture dissolved in water and diethylene glycol solution) to obtain the results shown in Table 8.

[0105] Table 9 Time to reach 80% of maximum height in manual mixing experiments for catalysts (in seconds)

[0106] Heat aging time (weeks) Time (seconds) %change 0 17.6 0.0 1 18.7 7.3 2 20.5 16.5 4 22.7 29.0

[0107] As shown in Table 9, the catalyst lost significant reactivity over a period of four weeks at 50°C. After four weeks of aging, the rise time increased by 29% from its original value.

[0108] The above experiments show that compounds IV and V in the present invention have good stability with HFO and have excellent industrial application value.

Claims

1. An amine catalyst for preparing a stable polyurethane foam system, characterized in that: The general structural formula of the amine catalyst is: Wherein, R1 is independently selected from one or more of the following groups: hydrogen, methyl, ethyl; R2 is independently selected from one or more of the following groups: methyl, tert-butyl; X is independently selected from one or more of the following groups: -O-, -N(CH3)-; p is 0 or 1; n and m are 0-4.

2. The amine catalyst according to claim 1, characterized in that: When X is -O-, R1 is hydrogen or methyl, R2 is hydrogen, and R3 is tert-butyl; or when X is -O-, R1 is hydrogen or methyl, R2 is methyl or ethyl, and R3 is methyl; or When X is -N(CH3)-, R1 is hydrogen, R2 is hydrogen, and R3 is tert-butyl.

3. The amine catalyst according to claim 1, characterized in that: The amine catalyst is n is 0-2.

4. A method for preparing an amine catalyst for preparing a stable polyurethane foam system, comprising the following steps: The raw material A is reacted with excess formaldehyde at 100-140°C in the presence of a metal catalyst.

5. The preparation method according to claim 4, characterized in that: The metal catalyst is a Ni-Cu-Cr catalyst.

6. Use of the amine catalyst as claimed in claim 1 in the preparation of a polyurethane foam system.

7. The use according to claim 6, characterized in that: The polyurethane foam system comprises a polyol resin blend and at least one polyisocyanate; wherein the polyol resin blend comprises the following components in parts by mass:

8. The use according to claim 7, characterized in that: The foaming agent is LBA foaming agent.

9. The use according to claim 7, characterized in that: The flame retardant is a phosphate flame retardant, chlorinated paraffin or melamine powder.

10. The use according to claim 7, characterized in that: The polyol resin blend also includes 0.01-5 parts of a foaming solubilizer.

Citation Information

Patent Citations

  • Amine catalysts for polyurethane foams

    US9550854B2